Pengaruh Pembelajaran Basis E-Learning Terhadap Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak di MA As Sathi’ Sedan - Moh Sholihuddin; Farida Isroani (Jurnal Bahastra, 2019)
e-learning is a new learning model carried out by the government to support student learning activities during the pandemic, this learning model is quite successful in developing in schools in Indonesia, especially Madrasah Aliyah As Sathi’, this is evidenced by the success of teachers in achieving the stages of learning through the e-learning model, but from that success there are still some symptoms that hinder the running of e-learning based learning itself, such as: Students who are reluctant to ask questions, lack of student interest when the material is delivered and students are still found who do not understand the subject matter. the material presented. In this study using a quantitative approach. The population in this study were students of class X Madrasah Aliyah As Sathi’ for the 2020/2021 academic year. Given the total number of students in class X is more than 100 people, the researchers took a sample of 25% of the total population. So this research is a sample study. In this study, the systematic data collection used an interview system to determine the use of the e-learning based learning model. The use of a questionnaire system to determine the effect of e-learning learning on learning outcomes and the use of report cards to determine student learning outcomes. The results of the study indicate that: (1) learning activities carried out by teachers of moral aqidah subjects through e-learning based learning are still considered less than optimal, this is evidenced by the results of a questionnaire of 24.5% which shows that students' low interest in learning through the model the basis of e-learning, (2) the calculation of the average value of students' learning outcomes or the average value of 89.8. This means that the average value of student learning outcomes in the moral aqidah subjects is categorized as very good, (3) the results of the discussion that have been submitted indicate that there is no effect of e-learning based learning on moral aqidah learning outcomes, the results obtained are 0.221. Where the value is significantly smaller than the "r" table, both at the 5% level and at the 1% level.